Retro peptide-hybrids as selective inhibitors of the Dengue virus NS2B-NS3 protease - Nitsche, Christoph; Behnam, Mira A. M.; Steuer, Christian; Klein, Christian D. (Antiviral research, 2012)
New chemotherapeutics against Dengue virus and related flaviviruses are of growing interest in antiviral drug discovery. The viral serine protease NS2B-NS3 is a promising target for the development of such agents. Drug-like inhibitors of this protease with high affinity to the target are not available at the moment. The present work describes the discovery of new retro di- and tripeptide hybrids that do not necessarily require an electrophilic “warhead” to achieve affinities in the low micromolar range. The most active sequence in this series is the tripeptide R-Arg-Lys-Nle-NH2. By variation of the N-terminal groups (R) it could be shown that the previously described arylcyanoacrylamide moiety is a preferable group in this position. Retro tripeptide hybrids were found to be more active and more selective than retro dipeptide hybrids. A significant selectivity towards the Dengue virus protease could be shown in a counterscreen with thrombin and the West Nile virus protease. Alternative sequences to R-Arg-Lys-Nle-NH2 did not have higher affinities towards the Dengue virus protease, similar to retro-inverse sequences with d-lysine and d-arginine residues. The results of a competition assay with the known inhibitor aprotinin indicate that the N-terminal arylcyanoacrylamide residue of this compound class binds near the catalytic center of the enzyme.